Analisis sajian buku ajar fisika sma kelas Xi semester 1 terkait komponen contextual teaching and learning (CTL) - Honi Helmiza; Desnita Desnita; Silvi Yulia Sari; Akmam Akmam (Universitas Negeri Padang, 2019)
The book acts as a source of independent learning, if learning is designed in full. Textbooks are said to be good, one of them is by fulfilling the components of the contextual approach as recommended in the 2013 curriculum. Contextual teaching books connect theories, phenomena and problems encountered so students can implement theories, concepts and principles that have been learned with everyday life. The purpose of this study was to find out whether the presentation of physics textbooks for Class XI High School 1 Semester 1 had facilitated the implementation of a contextual approach in high school. The type of research used is descriptive research and the approach used is a qualitative approach. The sampling technique uses purposive sampling. The research instrument used in this study was a statement sheet in the form of statements according. The data analysis technique used is the content analysis technique and processed with percentages. Based on the research conducted, it was found that the results of this study were presented in the fourth analysis of physics books in class XI in the first semester which facilitated the implementation of the contextual approach. The book that has been very facilitating and suitable for use by the school is Yrama Widya's book. The Yrama Widya book has the highest and stable value in each component of the CTL assessment with an average value of 82.3%. Whereas the book with the lowest score is Tiga Serangkai with an average value of 64.7% which is categorized as facilitating. Whereas from the CTL assessment component, the four books generally have the highest value on the modeling component and the lowest in reflection.